Impact of Service Quality on Increasing the Number of Sharia Pawnshop Customers in Aceh - Anwar Puteh; M. Rasyidin; Muhammad Authar ND; Nurul Mawaddah; Yulius Dharma (International Journal of Artificial Intelligence Research, 2022)
This study examines the effect of service quality on increasing the number of Sharia Pawnshop customers in Aceh Province. Service quality indicators are Tangibles, Empathy, Responsiveness, Reliability and Assurance. This study used primary data which were the results of the distribution of questionnaires to Sharia Pawnshop customers in Aceh Province as many as 100 respondents. Data analysis used multiple linear regression analysis. The results found that all service quality variables such as Tangibles, Empathy, Responsiveness, Reliability and Assurance had a positive and significant effect on increasing the number of Sharia pawnshop customers in Aceh Province. This proves that PT. Sharia Pawnshop (PT. Pegadaian Syariah) must pay attention to and improve the quality of services to increase the number of people, especially those in Aceh Province to become customers of the pawnshop and most importantly maintain the current number of customers.